Applications and Preparation Methods of Copper Chromite Catalysts: A Review - Ram Prasad; Pratichi Singh (Bulletin of Chemical Reaction Engineering & Catalysis, 2011)
In this review article various applications and preparation methods of copper chromite catalysts have been discussed. While discussing it is concluded that copper chromite is a versatile catalyst which not only catalyses numerous processes of commercial importance and national program related to defence and space research but also finds applications in the most concerned problem worldwide i.e. environmental pollution control. Several other very useful applications of copper chromite catalysts are in production of clean energy, drugs and agro chemicals, etc. Various preparation methods about 15 have been discussed which depicts clear idea about the dependence of catalytic activity and selectivity on way of preparation of catalyst. In view of the globally increasing interest towards copper chromite catalysis, reexamination on the important applications of such catalysts and their useful preparation methods is thus the need of the time. This review paper encloses 369 references including a well-conceivable tabulation of the newer state of the art. © 2011 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)